Physical and Mechanical Properties ofAcacia Mangium x Acacia Auriculiformis Hybrid (Acacia Hybrid) and Acacia Superbulk Planted in Sarawak - Farawahida, Binti Abu Zaharin (Universiti Malaysia Sarawak (UNIMAS), 2007)
Acacia mangium and Acacia aUriclilijormis are some of the most widely planted forest species in Malaysia. Recently, two new wood materials were introduced in Sarawak namely Acacia magillm x Acacia auriCliliformis (Acacia hybrid) and Acacia mangium superbulk which have desirnble characteristics of rapid growth rates and greater resistance to heart rot. Studies of their basic charncteristics are important for future utilization. The objectives of this study are to determine the mechanical and physical properties and to compare the properties of A. mangium, A. auriculijormis, A. hybrid and A. superbulk. Acacia trees of 6 years old were studied and sampled by cutttin~ at DBH, 50%, 70"10 and 100% height of the clear bole. Results showed that density of A. hybrid was 472 kglm-, A. mangium 464 kglm2 and A. superbulk 336 kglm3 . Static bending test showed that the modulus of rupture (MOR) of A. auriculijormis was 89 N/mm2, A. hybrid 85 N/mm2, A. mangillm 78 N/mm2 and A. superbulk 55 N/mm2 . For compression parallel to grain, the maximum crushing strength (MCS) ofA. hybrid was the highest (62 N/mm\ followed by A. auriclilijormis (59 N/mm\ A. mangium (53 N/mm2) and A. superbulk (50 N/mm2 ). The Young modulus value for all Acacia species studied showed statistically no significant difference. Acacia hybrid had higher strength than A. superbulk and its strength value was found to be not significantly difterent with A. auriculijormis. Genernlly, the strength properties among the Acacias varied in the following descending order of MOE and MOR values was A. allriculijormis highest, A. hybrid, A. mangium and A. superbulk. Based on vertical variation analyses it can be concluded that the lower part, 50% of the height and below, have better physical and mechanical properties than the upper part of the trees.